2017
DOI: 10.1186/s13052-016-0315-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice recommendations for allergen-specific immunotherapy in children: the Italian consensus report

Abstract: Allergen-specific immunotherapy (AIT) is currently recognized as a clinically effective treatment for allergic diseases, with a unique disease-modifying effect. AIT was introduced in clinical practice one century ago, and performed in the early years with allergenic extracts of poor quality and definition. After the mechanism of allergic reaction were recognized, the practice of AIT was refined, leading to remarkable improvement in the efficacy and safety profile of the treatment. Currently AIT is accepted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 124 publications
(109 reference statements)
0
57
0
4
Order By: Relevance
“…In order to reduce RTD hospitalizations, new treatments such as allergen-specific immunotherapy is promising. 33 In conclusion, this study provides useful information about pediatric RTD hospitalizations, thereby facilitating a greater understanding of this pathology, and, consequently, the implementation of these proven and evidence-based interventions. To direct future research, local health policy and guidelines could benefit from annual clinical records of health service use for respiratory diseases.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In order to reduce RTD hospitalizations, new treatments such as allergen-specific immunotherapy is promising. 33 In conclusion, this study provides useful information about pediatric RTD hospitalizations, thereby facilitating a greater understanding of this pathology, and, consequently, the implementation of these proven and evidence-based interventions. To direct future research, local health policy and guidelines could benefit from annual clinical records of health service use for respiratory diseases.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, smoking prevention and standardized management programs for RTD should be implemented in developing countries as early as possible. In order to reduce RTD hospitalizations, new treatments such as allergen‐specific immunotherapy is promising …”
Section: Discussionmentioning
confidence: 99%
“…Patients with suspected or confirmed infection with COVID-19 should discontinue the treatment [ 94 ]. Finally, in children with rhinoconjunctivitis caused by grass or birch, it has been shown that some SLIT products can be a feasible option not only for controlling symptoms, but also for preventing the onset of asthma [ 13 , 95 ]. A minimum of 3 years course is generally recommended to obtain a preventive effect [ 93 ].…”
Section: Indicationsmentioning
confidence: 99%
“…Subsequently, a remarkable number of clinical studies on SLIT was published showing indirectly an efficacy not far from that of SCIT [ 8 , 9 ] even if head-to-head studies are lacking. SLIT has been quickly recognized in official documents as an alternative to SCIT in respiratory allergy at variance from other routes [ 10 , 11 , 12 , 13 , 14 ]. Furthermore, SLIT has been used for other allergy-driven diseases, such as atopic dermatitis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…La IT es una opción terapéutica en pacientes con RA o rinoconjuntivitis con/sin asma alérgica con evidencia de sensibilización específica a IgE hacia aeroalérgenos clínicamente relevantes. 96,98,126 Está indicada en presencia de síntomas moderados a graves que interfieran con las actividades diarias habituales o el sueño a pesar de las medidas de evitación y la farmacoterapia (guías ARIA). 8,96,98 Dado que la IT es específica para los alérgenos utilizados, su eficacia depende de una identificación adecuada del o los alérgenos desencadenantes.…”
Section: Eficacia En Pediatríaunclassified